POLA SIMBIOTIK NEGARA DAN AGAMA DALAM PERSPEKTIF PERBANDINGAN HUKUM TATA NEGARA INDONESIA - Wahyuni (Qaumiyyah: Jurnal Hukum Tata Negara, 2021)
One of the issues in the field of religion that is of concern is global information disclosure which has an impact on violence in religion. Narrow interpretations of religion that give rise to conflicts between religious communities and between adherents of the same religion, especially in Indonesia, are experiencing dynamics that affect the state structure. Religious order and state order in Indonesia have a close relationship. Therefore, this paper seeks to provide an overview of how the position of religion in the state is from the perspective of constitutional law. The position of religion in the state can be seen in three patterns, namely the integralistic pattern, the symbiotic pattern and the secularistic pattern. Through the concept of the three patterns, it will provide a normative descriptive analysis of the position of religion in various countries in the world and its correlation to the effectiveness of law. Abstrak Salah satu isu dibidang agama yang menjadi perhatian adalah keterbukaan informasi global yang berdampak pada kekerasan dalam beragama. Penafsiran sempit terhadap agama yang memunculkan konflik antar umat beragama maupun antar sesama penganut agama yang sama khususnya di Indonesia mengalami dinamika yang mempengaruhi tatanan negara. Tatanan keagamaan dan tatanan negara di Indonesia memiliki hubungan yang erat. Olehnya tulisan ini berupaya memberikan gambaran bagaimana kedudukan agama dalam negara dengan perspektif hukum tata negara. Kedudukan agama dalam negara dapat dilihat pada tiga pola, yaitu pola integralistik, pola simbiotik dan pola sekularistik. Melalui konsep tiga pola tersebut akan memberikan deskriptif analisis secara normatif mengenai kedudukan agama dalam berbagai negara di dunia serta korelasinya terhadap efektivitas hukum.